The Effectiveness of Contextual based Textbooks on the Amount and Measurement Material of Class X Students of Tugumulyo Senior High School - Pransiska Pransiska; Ahmad Amin; Ovilia Putri Utami Gumay (Kasuari: Physics Education Journal (KPEJ), 2019)
The purpose of the research determine the learning outcomes for Class X Students of SMA Negeri Tugumulyo Academic Year 2019/2020 after using to physics-based teaching materials on the Scale And Measurement for Class X Students of SMA Negeri Tugumulyo Academic Year 2019/2020. Subjects in this study were all class X IPA and the subject of broad group research in this study was class X IPA 5 SMA Negeri Tugumulyo Academic Year 2019/2020 consisting of 33 students taken with simple random sampling technique. Data collection was done by tests. Daily test results 82% of students obtained scores above 73 out of 10 test items. Because of three there were students absent then the table value with degrees of freedom (dk) = n-1 = 30 ─ 1 = 29 and α = 0.05 t count = 2,80 and ttable = 1.699 because t count ≥ ttable then Ha is accepted. So it can be said that the developed contextual to the learning approach book is effective.